Randomized trial comparing the safety and antibody responses to live attenuated versus inactivated influenza vaccine when administered to breastfeeding women. Issue 31 (25th July 2018) - Brady, Rebecca C.; Jackson, Lisa A.; Frey, Sharon E.; Shane, Andi L.; Walter, Emmanuel B.; Swamy, Geeta K.; Schlaudecker, Elizabeth P.; Szefer, Elena; Wolff, Mark; McNeal, Monica Malone; Bernstein, David I.; Steinhoff, Mark C.
Highlights: Prospective, randomized, comparative trial of LAIV versus IIV in women who are actively breastfeeding infants. One (1%) possible transmission of LAIV from a mother to her infant who remained well. No LAIV virus was detected in human milk. Serum and breast milk antibody titers were higher in IIV compared to LAIV recipients. Abstract: Background: Live attenuated influenza vaccine (LAIV) and inactivated influenza vaccine (IIV) are both licensed for administration to nursing mothers. Little is known about the potential for transmission of LAIV viruses from the mother to the infant and the comparative breast milk antibody responses to LAIV and IIV. Methods: We performed a randomized, double-blind study comparing the immunogenicity of LAIV to IIV when administered to nursing mothers. The safety of LAIV to IIV in women and their infants was also compared. Women received LAIV + intramuscular placebo, or IIV + intranasal placebo on Day 0. Breast milk and nasal swabs (from women and infants) were collected on Days 0, 2, and 8 for detection of LAIV. Breast milk and serum antibody responses were measured at Days 0 and 28. The primary hypothesis was that LAIV would provide superior induction of breast milk IgA responses to influenza as compared to IIV when administered to nursing mothers. Results: Breast milk IgG, breast milk IgA (H1N1 only), serum hemagglutination inhibition (HAI), and serum IgG responses were significantly higher following administration of IIV compared to LAIV. Receipt of either LAIV or IIV was safe in women and their infants. One (1%) LAIV recipient transmitted vaccine virus to her infant who remained well. No influenza virus was detected in breast milk. Conclusions: Breast milk and serum antibody responses were higher for IIV compared to LAIV. LAIV and IIV were safe for nursing women but there was one (1%) possible transmission of LAIV to an infant. This study suggests that IIV may be the preferred vaccine for nursing mothers.